Zusammen arbeiten Praktiken der Koordination und Kooperation in kollaborativen Prozessen - Groth, Stefan 1982-; Ritter, Christian 1979- (transcript, 2019)
How are forms of cooperation negotiated and organized? Inside views into the concealed logics of collaborative research
Keywords: Art; Cooperation; Cultural Anthropology; Cultural Studies; Culture; Ethnografie; Ethnography; Kooperation; Kultur; Kulturanthropologie; Kultursoziologie; Kulturwissenschaft; Kunst; Sociology of Culture; Transdisciplinarity; Transdisziplinarität; SOCIAL SCIENCE / Anthropology / Cultural & Social; Kulturwissenschaften; Kooperatives Verhalten; Kollaboration; Koordination; Interdisziplinäre Forschung; Soziologie; Konferenzschrift -- 2017 -- Zürich